Upaya Meningkatkan Hasil Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe STAD Siswa Kelas V.A SD Negeri 146/IX Parit Kecamatan Sungai Gelam - Makhrus Makhrus (Universitas Batanghari Jambi, 2020)
This research aims to reveal information and discuss about efforts to improve mathematics learning outcomes through cooperative learning model type stad students grade V.A SD Negeri 146/IX Parit Sungai Gelam sub-district. This research is included in this type of class action research (PTK). This research was conducted at SD Negeri 146/IX Parit Sungai Gelam Sub-District. The study was conducted in the even semester of the 2018/2019 school year, starting in January 2019. The subjects in this study were students of Grade V.A. SD Negeri 146/IX Parit Sungai Gelam Sub-District which numbered 20 people. The research procedure consists of two cycles with each cycle twice meeting. Each cycle consists of four stages of research namely planning, implementation, observation and reflection. The data collection in this study was conducted using field records, student worksheets, written tests, and data analysis techniques using percentage formulas and data reduction. The results of this study show that the STAD Type Cooperative Learning Model can improve students' math learning outcomes by rewarding actions.